Extremely Broadband Topological Surface States in a Photonic Topological Metamaterial. Issue 20 (31st July 2019) - Kim, Minkyung; Gao, Wenlong; Lee, Dasol; Ha, Taewoo; Kim, Teun‐Teun; Zhang, Shuang; Rho, Junsuk
Abstract: Metamaterials, artificially engineered materials consisting of subwavelength unit cells, have shown potentials in light manipulation with their extraordinary optical properties. Especially, photonic topological metamaterials possessing topologically protected surface states enable extremely robust control of light. Here, an extremely broadband topological phase in photonic topological metamaterials is demonstrated. In particular, topological surface states are observed for all the frequencies below a certain cut‐off, originating from a double Weyl point at zero frequency. The extreme bandwidth and robustness of the photonic topological metamaterial are beneficial for practical applications such as one‐way waveguide and photonic integrated systems but also advantageous in design and fabrication since the only necessary condition is to satisfy the effective hyperbolic and chiral properties, without entailing strict periodic arrangement. Abstract : A photonic topological metamaterial supporting extremely broadband surface states with no lower limit is presented as opposed to previously reported topological surface states which have both lower and upper frequency limits. Backscattering immune surface states are demonstrated on the array of a double‐helix system. The extremely broad bandwidth and robustness are beneficial for practical applications such as photonic integrated circuitry.